Pelan pengurusan pembangunan persisir pantai pekan Kuah-Kelibang, Langkawi, Kedah : Laporan akhir - Asmawi, M. Zainora (PLANMalaysia, 2020)
The preparation of the report of 'Pelan pengurusan pembangunan persisir pantai pekan Kuah-Kelibang, Langkawi, Kedah' is undertaken to boost the economic development of the study area at the same time, the restoration of the environmental quality is given the emphasis, taking into consideration the development pressure of massive future development of reclamation projects. This report contains the aspect of physical and land use, economic sector, infrastructure and utility, transportation sector, the environmental sector, and governnance. The key stages involved: inception report, analysis report, and proposal report, addressing the pertinent findings that lead to the improvement works in the future.